DESIGN OF WEB-BASED VIRTUAL TOURISM INFORMATION SYSTEM AT GEOPARK CILETUH SUKABUMI - Elsa Ramadanti; Muhamad Muslih; Nunik Destria Arianti (Kresnamedia Publisher, 2022)
Geopark Ciletuh Sukabumi is an earth park with biodiversity such as geological, social, and cultural elements, to locations for research and tourism. Tourist destinations in the Ciletuh Geopark include waterfalls, beaches, mountain peaks, islands, cultural tourism, and biodiversity. Due to the lack of information media about tourist objects in the Ciletuh Geopark, not many tourists visit to enjoy the beauty of natural attractions and local cultural wisdom still maintained at the Ciletuh Geopark. Based on these problems, research was conducted to design and build a tourist information system with a virtual tour feature based on the Geopark Ciletuh Sukabumi website. In this study, the author designed the system using the Zachman Framework system development method and was built using CMS WordPress and Page Builder as well as PHP and MySQL programming languages. Testing the Virtual Tourism Information System at the Ciletuh Sukabumi Geopark using Blackbox Testing. The results of the design of a web-based virtual tourist information system at the Ciletuh Sukabumi Geopark can be used as a medium of tourist information for the general public and visitors who will travel to the tourist attraction.